Occupancy behaviour and patterns: Impact on energy consumption of high-rise households in southeast China - Zhang, Wuxia; Calautit, John Kaiser (Smart Energy, 2022)
With the rapid urbanization in China, energy consumption and corresponding carbon emissions in residential buildings are growing. Because occupant behaviour plays a significant role in building energy performance and occupant comfort, understanding the crucial links between occupant lifestyles and energy use is the key. Most studies on the relationship between occupancy behaviour and energy usage have been conducted in public or commercial buildings. Because data is difficult to obtain and key information about existing houses is required, research on high rise residential buildings is limited. To acquire information on thermal satisfaction, residential equipment ownership and usage habits and attitude to smart meters, this paper conducted a comprehensive survey of 112 metropolitan families living in a typical booming city. A case study high-rise residential building is modelled in a building energy simulation tool. The result is compared with the actual energy bill acquired from occupants or smart meters to better understand the energy usage in this area. The results showed that a large variation in energy use could exist in different households, which is influenced by several factors such as occupancy patterns and habits, as observed in the survey. At the same time, it shows the challenge of predicting the energy use of such a building with varying internal heat gains, set points and window opening behaviours across the different households.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.segy.2022.100072 5072953:NW2N9ZM9 openalex: W4280534598
Keywords: C:China; _z:class:countries; _z:class:themes; oa:keyword:energy consumption; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes